PRODUÇÃO DE MELÃO EM FUNÇÃO DA POPULAÇÃO E DAS COBERTURAS DE SOLO EM AQUIDAUANA/MS - Ketlin Queiróz Modesto , Emilly; Leandro da Silva , Maiele; Luis Carpinedo Gomez, Aurélio; Ferreira Marcelino , Adriele; Gustavo Silva Barros filho , Luís (ANAIS DO ENIC, 2026)
-